(untitled) (CAHIERS MAGELLANES-NS, 2024)
This article provides a detailed analysis of the foundations, principles, and directions of linguistic and lisonic classification. Lisonic classification focuses on the diversity of languages, systematicity, hierarchical structure, and evolutionary aspects. Linguistic classification, on the other hand, has a broader scope, encompassing the categorization of linguistic units based on phonetic, morphological, syntactic, and semantic features. The study also examines the differences between lisonic and linguistic classifications, their application areas, and the specific challenges in classifying linguistic units. Additionally, key aspects such as historical, cultural, and social contexts are considered in the classification processes. This research offers a theoretical and methodological foundation for linguistic studies, contributing to a deeper understanding of language diversity, structure, and evolution.